Risk and Vulnerability in Social Assistance Receipt of young adults in Finland - Ilmakunnas Ilari (Wiley-Blackwell Publishing Ltd., 2022)
Social background may affect not only individuals’ wellbeing, but also their ability to manage the typical and problematic transitions occurring during young adulthood. Hence, this article has used Finnish population register data to analyse how social background and critical life-course factors predict the number of months of social assistance received annually among young adults aged 19–29. Special interest was given to asking whether those with a disadvantaged social background are more vulnerable to the effects of critical life-course factors. The results showed that social background and critical life-course factors have independent effects on social assistance receipt. Additionally, this study shows that the effects and the incidence of critical life-course factors can be affected by social background.